2019
DOI: 10.2147/cmar.s218676
|View full text |Cite
|
Sign up to set email alerts
|

<p>Differential gene expression identifies KRT7 and MUC1 as potential metastasis-specific targets in sarcoma</p>

Abstract: BackgroundDespite numerous discoveries regarding the molecular genesis and progression of primary cancers, the biology of metastasis remains poorly understood. Compared to very large numbers of circulating tumor cells that are now known to accompany nearly all cancers, a relatively limited number of lesions actually develop in most patients with metastases. We hypothesized that phenotypic changes driven by differential gene expression in a finite subpopulation of tumor cells render those cells capable of metas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
3
10
0
Order By: Relevance
“…41 Interestingly, high expression level of MUC1 in sarcoma metastasis was correlated with worse overall survival in sarcoma. 26 Our result also correlated a high expression of MUC1 with low survival of OS patients (Figure 4(a)).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…41 Interestingly, high expression level of MUC1 in sarcoma metastasis was correlated with worse overall survival in sarcoma. 26 Our result also correlated a high expression of MUC1 with low survival of OS patients (Figure 4(a)).…”
Section: Discussionsupporting
confidence: 74%
“…The associations between differentially regulated (both upregulated and downregulated) genes and OS have already been analyzed (except RAB40C, USP11 , CTNNBIP1, TNC2, GCA, JAG2 , and KAZALD1 ). 2126 However, in these studies, the prognostic values of the genes have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…17 Although the direct links between KRT7 and the PC cell behaviors have been rarely studied, KRT7 has been widely reported to enhance growth and development of several cancers upon activation. 16,[34][35][36] In the present study, the subsequent rescue experiments suggested that overexpression of WT1 blocked the anti-tumor functions of miR-216a in PC cells; while silencing of KRT7 suppressed the oncogenic effects of WT1. In addition, either miR-216a upregulation or KRT7 silencing was found to suppress the phosphorylation of PI3K and AKT in PC cells, while WT1, as expected, activated the PI3K/ AKT signaling pathway, indicating that miR-216a mediates the WT1/KRT7 axis and impairs the PI3K/AKT pathway to suppress PC progression.…”
Section: Discussionsupporting
confidence: 56%
“…Likewise, stable high expression of KRT7 has been found in the clinical PC samples compared to the pseudotumoural chronic pancreatitis 17 . Although the direct links between KRT7 and the PC cell behaviors have been rarely studied, KRT7 has been widely reported to enhance growth and development of several cancers upon activation 16,34–36 . In the present study, the subsequent rescue experiments suggested that overexpression of WT1 blocked the anti‐tumor functions of miR‐216a in PC cells; while silencing of KRT7 suppressed the oncogenic effects of WT1.…”
Section: Discussionsupporting
confidence: 50%
“…Previous studies showed that KRT7 play a signi cant role in tumor metastasis and considered as prognostic biomarker and potential targets for therapeutic prevention of metastasis. [16] In addition, KRT7 was down-regulated and hypermethylated in CRC tissues compared with adjacent normal tissues and may lead to the occurrence of CRC. [26] 7) STK33 (Serine/threonine kinase 33) was experimentally demonstrated that downregulation and hypermethylation of STK33 in CRC tissues compared with normal tissues with P < 0.001, and STK33 methylation was also remarkably associated with lymph node metastasis, tumor invasion, distant metastases and tumor stage.…”
Section: Discussionmentioning
confidence: 99%